A stated preference analysis of real-time public transit stop information - CAULFIELD, BRIAN; O'MAHONY, MARGARET MARY (My University, 2009)
This paper presents the results of a study conducted to examine the benefits derived from real-time public transit stop information. This research examines the preferences between several options of receiving real-time public transit stop information. The literature states that one of the main reasons individuals access real-time information is to remove the uncertainty when using public transit. This relationship was examined to ascertain if the provision of real-time public transit information can remove the uncertainty and frustration associated with using public transit. A nested logit model structure was applied in this study to examine the benefits derived from accessing real-time public transit information. These models are estimated on segments of the dataset to ascertain how the mode of transport used by the respondents impacts the benefits derived from using real-time public transit information. The results of this study demonstrate that passengers derive the greatest benefit from accessing transit stop information from real-time information displays. Respondents were shown to obtain the second highest utility when accessing transit stop information via a mobile phone short message service (SMS). Bus users were found to gain the highest benefit from the provision of real-time transit stop information.
PUBLISHED
Keywords: transport; real-time information